Troponin T: Correlation with location and volume of acute brain infarction - Král, Michal; Šaňák, Daniel; Veverka, Tomáš; Hutyra, Martin; Vindiš, David; Bártková, Andrea; Kunčarová, Anna; Dorňák, Tomáš; Čecháková, Eva; Herzig, Roman; Langová, Kateřina; Kaňovský, Petr; et al. (International journal of cardiology, 2015)
BACKGROUND: The troponin T (cTnT) is frequently elevated in acute ischemic stroke (AIS) patients. However, the relationship, if any, between the cTnT level and brain infarction remains to be established. The aim was to investigate the possible correlation between the location and volume of brain infarction and the cardiac cTnT serum level in AIS patients. METHODS: The study consisted of consecutive AIS patients admitted within 12h of stroke onset. The location and volume of the acute ischemic lesion was assessed with magnetic resonance imaging. Standard laboratory tests, including cTnT and repeated electrocardiograms, were performed at admission and after 4h. Correlations between the cTnT level and the location and volume of brain infarction and baseline parameters were tested with a Spearman correlation coefficient. Univariate and multiple logistic regression analysis (LRA) were used to determine the possible predictors of cTnT elevation. RESULTS: Out of the 200 enrolled patients, elevated cTnT was present in 71 (36%). No correlation was found between the cTnT serum levels and the location (P>0.05) nor volume of brain infarction (r=0.05, P=0.48). LRA identified creatinine (OR: 1.26 per 10μmol/L increase; 95% CI: 1.043-1.524), NT-proBNP (OR: 1.05 per 100μg/L increase; 95% CI: 1.018-1.093) and male gender (OR: 3.674; 95% CI: 1.025-13.164) as significant independent predictors of pathological elevation of cTnT. CONCLUSIONS: Although elevated cTnT serum level is relatively frequent in AIS patients within the first 12h of stroke onset, it is not related to the location or volume of brain infarction. CLINICAL TRIAL REGISTRATION: http://www.clinicaltrials.gov (No. NCT01541163).
Keywords: Electrocardiography; Humans; lidé; hodnocení výsledků zdravotní péče; Statistics as Topic; magnetická rezonanční tomografie; Acute Disease; elektrokardiografie; lidé středního věku; Sex Factors; mozek; Magnetic Resonance Imaging; sexuální faktory; Outcome Assessment, Health Care; Time Factors; Middle Aged; Creatinine; časové faktory; Brain Infarction; Female; akutní nemoc; Male; Adult; troponin T; prognóza; Prognosis; mozkový infarkt; mužské pohlaví; Aged; ženské pohlaví; Reproducibility of Results; dospělí; Brain; statistika jako téma; kreatinin; Troponin T; reprodukovatelnost výsledků; senioři